Characterization of an Ovine Bilateral Critical Sized Bone Defect Iliac Wing Model to Examine Treatment Modalities Based on Bone Tissue Engineering. (16th February 2014) - Lansdowne, Jennifer L.; Devine, Declan; Eberli, Ursula; Emans, Pieter; Welting, Tim J. M.; Odekerken, Jim C. E.; Schiuma, Damiano; Thalhauser, Martin; Bouré, Ludovic; Zeiter, Stephan
Abstract : Critical sized bone defect (CSBD) animal models are used to evaluate and confirm efficacy and potency of new treatment modalities based on bone tissue engineering before the latter can be applied in clinical practice. In this study, a bilateral CSBD model in the iliac wings of sheep is described in detail. To demonstrate that this is a large animal CSBD model in sheep, bone healing within the defect left empty (negative control) or filled with autologous corticocancellous bone graft (clinical gold standard, positive control) was assessed using micro-CT, histology, histomorphometric, and fluorochrome analysis. After three months, new bone into the defect site was formed across the whole defect in the positive controls but limited to the edge of the defects in the negative controls. Bone volume in the positive controls was statistically higher than in the negative controls, with the latter having less than 10% new bone growth. There were no intraoperative or postoperative complications. The model described here represents a reliable and reproducible bilateral CSBD in sheep with low morbidity that can be used for in vivo evaluation of new treatment modalities based on bone tissue engineering.